Characteristics of Patients with Abdominal Trauma from January 1st 2019 to December 31st 2019 at Dr. Mohammad Hoesin General Hospital - Muhammad Fikri Aulia; Efman EU Manawan (Sriwijaya Journal of Surgery, 2021)
Background: Trauma is the main cause of death in the subgroup of patients under 40 years of age. The main cause of death. Abdominal trauma ranks third as a cause of death due to trauma after head and chest injuries. The classification of abdominal trauma based on the type of trauma is divided into two, namely sharp trauma and blunt trauma. The aim of this study is to investigate the characteristics of abdominal trauma patients at dr. Mohammad Hoesin Palembang General Hospital. Methods: This research was a retrospective descriptive study. Using secondary data from the medical records of Mohammad Hoesin Hospital, Palembang. Performed in the from January 2019 to December 2019. Samples inculded were all patients diagnosed with abdominal trauma, underwent laparotomy, and hospitalized in digestive surgery wards. Results: There were 33 subjects participated who met study critera. The highest age group for abdominal trauma was at the age group 26-45 years as many as 16 people. Abdominal trauma patients were mostly found in the male, with 32 people (97%). Based on their causes of abdominal trauma, most of them were caused by stab wounds as many as 16 people (48.5%). In abdominal trauma patients based on the type of trauma, most of them occurred due to sharp trauma, with 23 people (69.7%). The organs most frequently injured due to abdominal trauma were the small intestine and large intestine, with 14 people (42.4%). The length of stay of patients with abdominal trauma varies from 1 day to 22 days, with the most length of stay between 0-7 days as many as 20 cases (60.6%). Conclusion: Male patients, aged 26–45-year-old, caused by stab wound, sharp trauma, affecting small and large intestine, and hospitalized up to 7 days are the most common characteristic of patients diagnosed with abdominal trauma.